2016
DOI: 10.1038/srep32920
|View full text |Cite
|
Sign up to set email alerts
|

High correlation of Middle East respiratory syndrome spread with Google search and Twitter trends in Korea

Abstract: The Middle East respiratory syndrome coronavirus (MERS-CoV) was exported to Korea in 2015, resulting in a threat to neighboring nations. We evaluated the possibility of using a digital surveillance system based on web searches and social media data to monitor this MERS outbreak. We collected the number of daily laboratory-confirmed MERS cases and quarantined cases from May 11, 2015 to June 26, 2015 using the Korean government MERS portal. The daily trends observed via Google search and Twitter during the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 24 publications
3
113
1
4
Order By: Relevance
“…This moving average method used to facilitate the trends comparison among datasets. Time-lag correlation was utilized to assess whether J o u r n a l P r e -p r o o f the raised of GT data were correlated with the following increased of COVID-19 cases, as previously applied in other study (Shin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This moving average method used to facilitate the trends comparison among datasets. Time-lag correlation was utilized to assess whether J o u r n a l P r e -p r o o f the raised of GT data were correlated with the following increased of COVID-19 cases, as previously applied in other study (Shin et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Predicting the development of the outbreak as early and as reliably as possible is critical for action to prevent its spread. Internet searches and social media data have been reported to correlate with traditional surveillance data and can even predict the outbreak of disease epidemics several days or weeks earlier [4][5][6][7][8][9].…”
mentioning
confidence: 99%
“…This observation further suggests that results of Twitter studies based on an English-only corpus may not always be generalizable to non-English-speaking Twitter users. Recent research identified significant correlation between the normalized volume of tweets with one of three Korean MERS-related keywords with number of laboratory-confirmed MERS cases in the outbreak [17]. Our study extended the existing literature on Twitter and MERS in Korea by going beyond the English and Korean languages by including tweets in Indonesian, Japanese and Thai.…”
Section: Discussionmentioning
confidence: 59%